Institutions, Comparative Advantage, and the Environment - Shapiro, Joseph S (Review of Economic Studies, 2025)
Abstract This paper proposes that strong institutions provide comparative advantage in clean industries, and thereby improve a country’s environmental quality. I study financial, judicial, and labour market institutions. Five complementary tests evaluate and assess implications of this hypothesis. First, industries that depend on institutions are clean. Second, strong institutions increase relative exports in clean industries. Third, an industry’s complexity helps explain the link between institutions and clean goods. Fourth, cross-country differences in the composition of output between clean and dirty industries explain an important share of the global distribution of emissions. Fifth, a quantitative general equilibrium model indicates that strengthening a country’s institutions decreases its pollution through relocating dirty industries abroad, though increases pollution in other countries. The comparative advantage that strong institutions provide in clean industries gives one under-explored reason why developing countries have relatively high pollution levels.